Belief in marriage the evidence for reforming weddings law. (BRISTOL UNIVERSITY PRESS, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. In principle, couples getting married in England and Wales can choose to do so in a way that reflects their beliefs. In practice, the possibility of doing so varies considerably depending on the religious or non-religious beliefs they hold. To demonstrate this divergence, this book draws on the accounts of 170 individuals who had, or led, a wedding ceremony outside the legal framework. The authors examine what these ceremonies can tell us about how couples want to marry, and what aspects of the current law preclude them from doing so. This new evidence shows how the current law does not reflect social understandings of what makes a wedding meaningful. As recommended by the Law Commission, reform is urgently needed.